New diagnostic ratios based on phenanthrenes and anthracenes for effective distinguishing heavy fuel oils from crude oils. Issue 1 (15th May 2016) - Zhang, Haijiang; Wang, Chuanyuan; Zhao, Ruxiang; Yin, Xiaonan; Zhou, Hongyang; Tan, Liju; Wang, Jiangtao
Abstract: The heavy fuel oils (HFOs) and crude oils are the main oil types in the marine oil spill accidents in China. It is usually a challenge to distinguish the HFOs from crude oils due to the highly similar physicochemical characteristics. In this paper, the distributions of phenanthrene (Phe), anthracene (Ant), methyl-phenanthrene (MP) and methyl-anthracene (MA) in hundreds of HFOs and crude oils samples which were collected from all over the world were characterized. Nine new diagnostic indexes, such as Ant/(Ant + Phe) and other eight diagnostic ratios based on the MP isomers and MA, were developed for effective distinguishing HFOs from crude oils. The histogram with normal fit plots, the double ratio plots and Bayes discriminant analysis (BDA) method were employed to illustrate the effectiveness of the new diagnostic indexes. BDA model based on nine new diagnostic indexes demonstrated high precision with discriminant ratio which lay between 93.92% and 99.32%. Highlights: The distributions of phenanthrene, anthracene, methyl-phenanthrene and methyl-anthracene in HFOs and crude oils were studied. Nine new diagnostic ratios were developed for effective distinguishing HFOs from crude oils. Bayes discriminant analysis demonstrated high precision with discriminant ratio lied between 93.92% and 99.32%.